The effects of substrate stiffness on the morphology, intercellular tension, and differentiation of vascular smooth muscle cells (Analysis of the surface microstructure and tension of cells using atomic force microscopy) - Kazuaki NAGAYAMA; Kouhei NISHIMIYA (Nihon Kikai Gakkai ronbunshu, 2018)
Vascular smooth muscle cells (VSMCs), one of the main components of arterial walls, actively remodel arterial wall in which they reside through biomechanical signals applied to themselves. The contractile or differentiated VSMCs were observed in normal blood vessels. In pathological vascular conditions, they dedifferentiated from contractile to a non-contractile or synthetic cells, and a similar change is observed when VSMCs are placed in culture conditions. The mechanisms regulating VSMC differentiation remain unclear at this stage. Here we investigated the effects of substrate stiffness on the morphology, intercellular tension, and differentiation of VSMCs. Rat VSMCs were cultured on the polyacrylamide gels, whose elastic modulus was 15 kPa, 40 kPa, and 85 kPa. Using fluorescent microscopy image-based analysis, and nano-indentation imaging with atomic force microscopy, we found that cell spreading and cell stiffening was induced by substrate stiffening in VSMCs. Interestingly, VSMCs on the substrates with middle stiffness (40 kPa) showed significant elongation and shape polarization, and their expression ratio of α-SMA with F-actin cytoskeleton was significantly higher than that of the cells on the other substrates. These results indicate that there exists an optimal substrate stiffness to promote VSMC differentiation, and cell shape polarization might be a key factor for VSMC differentiation.